A new species of Tenthras from Central America and new records of Cerambycinae (Coleoptera, Cerambycidae) from Belize - Bezark, Larry G. (Zootaxa, 2025)
A new species, Tenthras centralis is described from Guatemala and Belize. Country records are provided for 52 species newly recorded from Belize: Amphelictus hovorei Eya & Chemsak, 2003; Coleoxestia nitida (Bates, 1872); Poeciloxestia lanceolata Fragoso, 1978; Jupoata rufipennis (Gory, 1831); Megacyllene angulata (Fabricius, 1775); Neoclytus acteon (Chevrolat, 1860); Pirangoclytus mundus (Chevrolat, 1860); Pirangoclytus latithorax (Martins & Galileo, 2008); Unaiuba vitellina (Martins & Galileo, 2008); Ornithia mexicana (Sturm, 1843); Beraba piriana Martins, 1997; Eburia aegrota Bates, 1880; Eburia cubae Fisher, 1932; Eburia hovorei Noguera, 2002; Eburia stigma (Olivier, 1800); Eburodacrys asperula Bates, 1880; Eburodacrys triocellata (Stål, 1857); Pantomallus fuligineus Bates, 1872; Niophis antennata (Martins, Chemsak & Linsley, 1966); Aneflus (Protaneflus) minutivestis Chemsak & Linsley, 1963; Anelaphus eximius (Bates, 1885); Anelaphus giesberti Chemsak & Linsley, 1979; Anelaphus inermis (Newman, 1840); Mallocera spinicollis Bates, 1872; Nephalioides nigriventris (Bates, 1874); Poecilomallus palpalis Bates, 1892; Psyrassa bicolor García & Toledo, 2022; Psyrassa subpicea (White, 1853); Psyrassa xestioides (Bates, 1872); Trichophoroides albisparsus (Bates, 1872); Anatinomma alveolatum Bates, 1892; Heteraneflus castaneus Chemsak & Linsley, 1963; Gnomidolon basicoeruleum Martins, 1962; Ozodes multituberculatus Bates, 1870; Ozodes xanthophasma Bates, 1872; Coscinedes gracilis Bates, 1885; Obrium albifasciatum Bates, 1872; Atenizus laticeps Bates, 1867; Atenizus simplex Bates, 1884; Bromiades brachyptera (Chevrolat, 1838); Forficuladeres sexualis (Linsley, 1934); Dihammaphora dispar Chevrolat, 1859; Euderces velutinus (Fisher, 1931); Tetranodus reticeps (Bates, 1880); Gigantotrichoderes flabellicornis (Zajciw, 1965); Engyum virgulatum (Bates, 1880); Heterachthes wappesi Martins & Napp, 1986; Neocompsa alacris (Bates, 1885); Neocompsa mexicana (Thomson, 1865); Neocompsa thelgema Martins, 1971; Compsibidion vanum (Thomson, 1867); and Diasporidion duplicatum (Gounelle, 1909).